PENGEMBANGAN BUKU SUPLEMEN MUTASI GEN PADA MATAKULIAH GENETIKA - Harissudin Masrur; Aloysius Duran Corebima; Abdul Ghofur (Pascasarjana Universitas Negeri Malang, 2017)
Nontext book are books which are not used directly as a book to study particular subject in educational institution. One of nontext books is a supplementary book. Genetics course is a course taught in Biology Education Program of Jember University. There are several problems in the lecture based on the analysis of teaching materials needs. These problems are such as the source of many teaching materials that use English, so the students get difficult in understanding the material, students are looking forward to the material with a simple language and easy to understand, and having interesting illustrations. The purpose of this study is to produce a supplementary book of Genetics in Biology Education Program in University of Jember. The supplementary book which was being developed is a research-based supplementary book with development model R&D Borg and Gall. The supplementary book was validated by a material expert, a development expert, and tested on a small group of 15 students. The result of material validation showed the value of 81,39%, developing validation 97,96%, and the result of reading test 73,66%. Overall, the supplementary book is valid enough with a little revision. The revised book is based on suggestions and comments provided by validators and test of small group of students. Nontext book are books which are not used directly as a book to study particular subject in educational institution. One of nontext books is a supplementary book. Genetics course is a course taught in Biology Education Program of Jember University. There are several problems in the lecture based on the analysis of teaching materials needs. These problems are such as the source of many teaching materials that use English, so the students get difficult in understanding the material, students are looking forward to the material with a simple language and easy to understand, and having interesting illustrations. The purpose of this study is to produce a supplementary book of Genetics in Biology Education Program in University of Jember. The supplementary book which was being developed is a research-based supplementary book with development model R&D Borg and Gall. The supplementary book was validated by a material expert, a development expert, and tested on a small group of 15 students. The result of material validation showed the value of 81,39%, developing validation 97,96%, and the result of reading test 73,66%. Overall, the supplementary book is valid enough with a little revision. The revised book is based on suggestions and comments provided by validators and test of small group of students. Buku nonteks pelajaran merupakan buku-buku yang tidak digunakan secara langsung sebagai buku untuk mempelajari salah satu bidang studi di lembaga pendidikan. Salah satu jenis buku nonteks adalah buku suplemen. Matakuliah Genetika adalah matakuliah yang diajarkan di Program Studi Pendidikan Biologi Universitas Jember. Terdapat beberapa permasalahan didalam perkuliahan tersebut berdasarkan analisis kebutuhan bahan ajar. Permasalahan tersebut diantaranya adalah sumber bahan ajar banyak yang menggunakan bahasa Inggris sehingga mahasiswa merasa kesulitan dalam memahami materi, mahasiswa sangat mengharapkan materi dengan bahasa yang sederhana dan mudah dipahami, dan disertai ilustrasi menarik. Tujuan penelitian ini adalah untuk menghasilkan buku suplemen bahan ajar mata kuliah Genetika di Program Studi Pendidikan Biologi Universitasi Jember Buku suplemen yang dikembangkan merupakan buku suplemen yang berbasis penelitian dengan model pengembangan R&D Borg and Gall. Buku suplemen divalidasi oleh ahli materi, ahli pengembangan, dan diuji coba pada kelompok kecil dengan 15 mahasiswa. Hasil validasi materi menunjukkan nilai 81,39%, validasi pengembangan buku 97,96%, dan hasil uji keterbacaan 73,66%. Secara keseluruhan buku yang dikembangkan dalam kategori valid dan cukup valid dengan sedikit revisi. Revisi buku dilakukan berdasarkan saran dan komentar yang diberikan oleh validator dan mahasiswa uji coba kelompok kecil.